2010
DOI: 10.1039/c0cs00035c
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation peptide nanomaterials: molecular networks, interfaces and supramolecular functionality

Abstract: With improved understanding of the design rules for self-assembling peptides, new challenges will be faced to incorporate these materials into dynamic systems of higher complexity and functionality. In this highlight article we discuss very recent advances in these areas. Three areas are covered: (i) molecular networks based on peptides and their interactions including (bio-) catalytically driven systems; (ii) supramolecular functionality, both in the context of biological and nanotechnology applications; (iii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
179
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(183 citation statements)
references
References 102 publications
1
179
0
3
Order By: Relevance
“…Aptamer-functionalized nanotube electrodes have been shown to detect single bacterial cells in real time 26 . Further, we have recently shown that phage display can be utilized to determine peptide sequences that selectively bind to CNTs and graphene 8,[27][28][29] . This has enabled the generation of bifunctional peptides containing a carbon nanomaterial recognition moiety combined with an analyte binder to non-covalently selfassemble and impart selectivity on graphene sensor arrays.…”
mentioning
confidence: 99%
“…Aptamer-functionalized nanotube electrodes have been shown to detect single bacterial cells in real time 26 . Further, we have recently shown that phage display can be utilized to determine peptide sequences that selectively bind to CNTs and graphene 8,[27][28][29] . This has enabled the generation of bifunctional peptides containing a carbon nanomaterial recognition moiety combined with an analyte binder to non-covalently selfassemble and impart selectivity on graphene sensor arrays.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Assembly can be triggered by environmental variables such as pH, temperature, and salt concentration. [9][10][11] The morphology of self-assembled peptidic aggregates can be tuned by the amino acid sequence, and endowed with useful electronic and optoelectronic properties by the incorporation of aromatic groups into the peptide backbone that establish inter-peptide π -conjugation upon assembly. [10,12,13] The resultant electrical and electronic propertieselectron transport or exciton coupling, for example -provide the basis for a diverse array of organic electronic devices, such as light-emitting diodes, field-effect transistors, and solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] The morphology of self-assembled peptidic aggregates can be tuned by the amino acid sequence, and endowed with useful electronic and optoelectronic properties by the incorporation of aromatic groups into the peptide backbone that establish inter-peptide π -conjugation upon assembly. [10,12,13] The resultant electrical and electronic propertieselectron transport or exciton coupling, for example -provide the basis for a diverse array of organic electronic devices, such as light-emitting diodes, field-effect transistors, and solar cells. [14][15][16][17][18] Deterministic control of the structure, stability, and kinetics of self-assembled organic electronics by tuning monomer chemistry and environmental conditions presents a powerful route to the fabrication of 'designer materials' possessing desirable structural and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy has proven to be efficient for engineering specific nano-to microscopic architectures, amongst which fibrillar systems appear to dominate. [10,11] In part, this is because fiber formation is a single-mode polymerization process that is relatively straightforward to emulate, in part, because of the significance it has in normal and pathological cellular processes. However, for engineering and biomedical purposes fiber architectures impose strict limitations.…”
Section: Introductionmentioning
confidence: 99%